Strengthening the Euro Area : The Role of National Structural Reforms in Building Resilience - Bluedorn, John (Staff Discussion Notes; Staff Discussion Notes ;, 2019)
Cross-country differences in economic resilience-in an economy's ability to withstand and adjust to shocks-remain significant in the euro area. In part, the differences reflect the lack of a national nominal exchange rate as a mechanism to adjust to shocks. The IMF staff has argued that union-wide architectural changes such as the banking union, the capital markets union, and a central fiscal capacity can help foster greater international risk sharing. Yet even these changes cannot insure against all shocks. National policies thus have a vital role to play. This IMF staff discussion note analyzes how national structural policies can help euro area countries better deal with economic shocks. Using a mix of empirical and modeling approaches, the note finds that growth-enhancing reforms to labor and product market regulations, tailored to country-specific circumstances, would help individual euro area economies weather adverse shocks. Higher-quality insolvency regimes are associated with more efficient factor reallocation following a shock. The note also finds that structural and cyclical policies interact. Greater rigidities make economies more fragile, putting a higher burden on fiscal policy. This is especially true for members of a monetary union. Countries should build fiscal space in good times and tackle rigidities, reducing their need for countercyclical policies in bad times while making countercyclical policies more effective when deployed.